HUBUNGAN ANTARA PERHATIAN ORANG TUA DAN GAYA BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA - Isnaning Sari; Esti Harini (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
Descriptively, the purpose of this study is to know the tendency of parents attention, learning style and the learning mathematics achievement of the students of VIII Grade of all SMP (Junior High School) in Berbah district on 2013/2014 academic year. Correlatively, the purpose is to determine the relationship between parents attention and learning style with the learning mathematics achievement of the students of VIII Grade of all SMP (Junior High School) in Berbah district on 2013/2014 academic year. The population of this study was all students of VIII Grade of SMP (Junior High School) in Berbah district on 2013/2014 academic year. The sampling technique used was cluster random sampling technique. The researcher took and selected 2 classes of SMP N 3 Berbah, 1 class of SMP N 2 Berbah and 1 class of SMP Muhammadiyah Berbah as the sample class with the number of respondens is 110 students. The data analysis is using multiple correlation and multiple regression of two variables. The result of this descriptive study showed that the tendency of parents attention is on the medium category, while the learning stayle is on medium category and the learning mathematics achievement in a high category. From the calculation of multiple correlation test, the value of R = 0,660 and the significant value is 0,000 < 0,05, it means that there is a positive and significant relationship between parents attention and learning style with learning mathematics achievement.